Department of Biology, College of Science, University of Baghdad, Baghdad, Iraq - Hannon, Ahmed Y.; Al-Obaidi , Mohammed J.; Al-Khafaji, Samer S.; Jassim, Iftikhar Abdulwahab (Iraqi Journal of Science, 2022)
The recent study was conducted to measure some heavy metal content in potato and corn chips in Baghdad markets. Samples were analyzed by Atomic Absorption Spectrophotometer (AAS). Four metals, Cobalt (Co), Cadmium (Cd), Cupper (Cu) and Lead (Pb) were determined. Two types belonging to two manufacturer resources and two trademarks for each resource were tested in this work. Generally, the study recorded that the potato chips were containing metals less than the corn chips. According to Iraqi criteria, all tested types of potato chips were under the allowed levels. The mean of accumulation trend for both types was: Cu>Co>Pb>Cd. The mean of accumulation trend for the corn types of chips was: Baz>Pufack> Fantasia > Snack. The mean of accumulation trend for Potato chips was: Hlla>Mrsticks>Shepisco>Leez. Only Pufack (Jordan) Baz and Fantasia (Iraq) trademarks were containing levels of Cu exceeded of criteria. The aim of study is to monitor the levels of metals in chips food.